The End of Black and White. - Geer, Daniel E.
It's no longer just black hats or white hats in computer security. The more someone has to lose, the less likely they should be to trust the computer. It means that all people, all programs, all transactions are shades of grey. Black and white are just a memory.
Keywords: Black hat; Secure computing; Trust; White hat